Match-All Party: Pragmatisme Politik dan Munculnya Spesies Baru Partai Politik di Indonesia Pasca Pemilu 2009 - Aminuddin, M. Faishal; Ramadlan, Moh. Fajar Shodiq (UI Scholars Hub, 2015)
Indonesia’s democratization resulted in a uniqueness in party development. After the 2009 elections, new political party species which previously not represented and appears in western democracies, was raised. This article investigates the correlation between political pragmatism with adaptive party change in the electoral contest as well as in the parliament following the election. An important finding of this study is the emergence of species of match-all party that exist in pragmatic political conditions. It is proved that democratization in developing countries has a dynamic route. In streng¬thening these findings, an analysis of the dynamics of political parties also delivered. How parties maintaining their image in front of the public and at the same time shaping their patterns of interaction in government and parliament.